2019
DOI: 10.1186/s12864-019-6296-7
|View full text |Cite
|
Sign up to set email alerts
|

Population history and genetic adaptation of the Fulani nomads: inferences from genome-wide data and the lactase persistence trait

Abstract: BackgroundHuman population history in the Holocene was profoundly impacted by changes in lifestyle following the invention and adoption of food-production practices. These changes triggered significant increases in population sizes and expansions over large distances. Here we investigate the population history of the Fulani, a pastoral population extending throughout the African Sahel/Savannah belt.ResultsBased on genome-wide analyses we propose that ancestors of the Fulani population experienced admixture bet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
70
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 64 publications
11
70
2
Order By: Relevance
“…Previously published data from autosomal SNP arrays and whole‐genome studies largely corroborate the genetic structure of Sahelian populations as inferred here from uniparental markers, that is, the presence of an eastern Sahelian and western Sahelian genetic component with an admixture zone in the Lake Chad basin, observed in our data, is in agreement with the findings of Triska et al (). Autosomal‐based studies also point to a unique genetic composition and low population stratification in the Fulani and to a West African genetic background of the Songhai (Triska et al, ; Vicente et al, ). Our data on uniparental markers, on the other hand, indicate differences in the population histories of male and female subpopulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously published data from autosomal SNP arrays and whole‐genome studies largely corroborate the genetic structure of Sahelian populations as inferred here from uniparental markers, that is, the presence of an eastern Sahelian and western Sahelian genetic component with an admixture zone in the Lake Chad basin, observed in our data, is in agreement with the findings of Triska et al (). Autosomal‐based studies also point to a unique genetic composition and low population stratification in the Fulani and to a West African genetic background of the Songhai (Triska et al, ; Vicente et al, ). Our data on uniparental markers, on the other hand, indicate differences in the population histories of male and female subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that in the populations of eastern and central Sahel there is a discernible Eurasian genetic component introduced over a long period of time by numerous migration events from different non‐African regions (Galego Llorente et al, ; Haber et al, ; Pickrell et al, ). Successive waves of migration are clearly reflected in both maternal and paternal genetic pools (Bučková et al, ; Černý et al, ; Podgorná et al, ; Shriner & Rotimi, ) and also in autosomal datasets as shown by allele frequency based methods (Triska et al, ; Vicente et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the Fulani acquired the −13910*T haplotype by admixing with a North African population which had some Eurasian ancestry, so that this variant in the Fulani population has the same descent as the variant found in Eurasia (Coelho et al, 2005; Mulcare et al, 2004; Ranciaro et al, 2014). Furthermore, it has been estimated that two distinct admixture events took place, one 1,828 and the other 302 years ago (Vicente et al, 2019). Our estimates of the growth and selection of −13910*T haplotype in the Fulani indicate an earlier dating than the abovementioned admixture times (Vicente et al, 2019) and are consistent rather with the estimates of Coelho et al (2005), who proposes a period of 10,125–6,060 years ago.…”
Section: Discussionmentioning
confidence: 99%
“…Based on (probably different) Fulani DNA samples but again from northern Cameroon, it has been demonstrated that their −13910*T variant shares its haplotype backgrounds with Europeans (Coelho et al, 2005; Ranciaro et al, 2014), which suggests a single mutation event for this mutation and its introduction via admixture of non‐African sources and through gene flow. A recent study of Fulani pastoralists from Ziniaré, Burkina Faso (Vicente et al, 2019) confirmed these suggestions and showed that this variant shares its haplotype background with Eurasians and that ancestors of the Fulani probably acquired the haplotype via recent admixture events which took place in northern Africa.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation